2006
DOI: 10.1001/archpsyc.63.6.611
|View full text |Cite
|
Sign up to set email alerts
|

Frontal Responses During Learning Predict Vulnerability to the Psychotogenic Effects of Ketamine

Abstract: These findings relate aberrant prediction error-dependent associative learning to referential ideas and delusions via a perturbation of frontal cortical function. They are consistent with a model of delusion formation positing disruptions in error-dependent learning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
177
3
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 172 publications
(208 citation statements)
references
References 73 publications
21
177
3
5
Order By: Relevance
“…Consistent with these results, previous studies have reported the effect of other psychotogenic substances such as ketamine on the processing of salient information (Corlett et al, 2006). It has been suggested that the psychotropic effects of ketamine might also be related to alterations in the connectivity between specific brain regions, which has been demonstrated both in animal (Bolton et al, 2012) and in human studies (Salvadore et al, 2010).…”
Section: Discussionsupporting
confidence: 76%
“…Consistent with these results, previous studies have reported the effect of other psychotogenic substances such as ketamine on the processing of salient information (Corlett et al, 2006). It has been suggested that the psychotropic effects of ketamine might also be related to alterations in the connectivity between specific brain regions, which has been demonstrated both in animal (Bolton et al, 2012) and in human studies (Salvadore et al, 2010).…”
Section: Discussionsupporting
confidence: 76%
“…Here, we found that the MMN slope under placebo showed a negative correlation with the subsequent ketamine-induced extent of cognitive impairments across subjects; in contrast, no comparable relationship was found for psilocybin. Although this result is in accordance with Umbricht's MMN study (Umbricht et al, 2002), it may not appear to be fully consistent with the results by Corlett et al (2006), who found that frontal PE signals under placebo, measured during an associative learning task with fMRI, exhibited a positive correlation with the severity of positive symptoms (delusions, perceptual aberrations) under ketamine. However, the results from the two studies are not directly comparable owing to a number of major methodological differences, including different symptom rating scales, different ketamine dosage and application regimens, different measurement techniques (fMRI vs EEG), and, perhaps most importantly, fundamentally different cognitive paradigms.…”
Section: S-ketamine-induced Cognitive Impairmentscontrasting
confidence: 64%
“…This approach is inspired by the general notion that the development of psychiatric disease may result from the interplay between the (genetically determined) susceptibility of an individual and the expose to environmental stressors (Brown, 2011), and follows previous studies, which examined whether physiological markers can predict the individual degree of psychotic symptoms in drug-induced psychosis and schizophrenia (Corlett et al, 2006;Honey et al, 2008;Krystal et al, 2003;Umbricht et al, 2002). Here, we found that the MMN slope under placebo showed a negative correlation with the subsequent ketamine-induced extent of cognitive impairments across subjects; in contrast, no comparable relationship was found for psilocybin.…”
Section: S-ketamine-induced Cognitive Impairmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute administration of ketamine in healthy volunteers impairs performance on memory and cognitive tasks and also induces psychotic symptoms such as delusions and dissociative sensations (Krystal et al, 1994;Morgan et al, 2004a). Neuroimaging studies have reported that acute ketamine administration is associated with taskrelated reductions in prefrontal cortical activation, as measured by blood oxygenation level-dependent (BOLD) response (Corlett et al, 2006;Corlett et al, 2007). Frequent ketamine use has been found to be associated with persistent working memory and executive function impairment and psychotic-like symptoms (Morgan et al, 2004b(Morgan et al, , 2010.…”
Section: Introductionmentioning
confidence: 99%